Case report: A relatively rare adverse event caused by carbetocin— placenta interception - Li, Jun-Qiang; Zhan, Yong-Chi; Wang, Xiao-Dong (Frontiers in Pharmacology, 2023)
Placenta interception is extremely rare, and herein, we report the case of a 33-year-old woman with placenta interception during cesarean section caused by carbetocin, which was intravenously injected immediately after delivery of the infant to prevent postpartum hemorrhage. There was no sign of placental separation in the third stage of labor. A protuberance with gross subserous blood vessels in the left fundus of the uterus was detected and was misdiagnosed as placental accreta. The patient was transferred to the district referral hospital to manage the protuberance after stitching up the incision. On opening the original incision in the tertiary hospital, the protuberance disappeared, and the placenta was found in the lower segment of the uterus cavity. The intercepted placenta showed a spontaneous resolution from the uterine wall and was removed intact. This case report details the typical presentation of placenta interception to make obstetricians aware of the possibility that carbetocin might lead to this adverse event.